Response of Canola Advanced Lines to Delay Plantings upon Late Season Drought Stress - Shirani Rad, Amir Hosein; Shahsavari, Nasser; Safavi Fard, Nadia (Journal of Scientific Agriculture, 2017)
In order to evaluation of canola advanced lines response to delay plantings under late season drought stress conditions, an experiment was carried out in a factorial split-plot arrangement based on RCBD with three replications during two years (2012-2014) in Karaj of Iran. Treatments were; (1): Planting date in two levels (16 October and 1 November), (2): irrigation, in two levels (I1: normal irrigation as control and I2: restricted irrigation after pod formation stage) as main plots and (3): twelve oilseed rape genotypes as sub plots such as BAL2, BAL1, BAL3, BAL6, BAL8, BAL9, BAL11, BAL15, L72, R15, L109 and Okapi. The interaction effects of planting date, irrigation and genotype on pod number per plant, seed number per pod, 1000-seed weight, seed yield, and oil yield were significant at 1% level probability. The maximum seed yield under planting at the appropriate time (16 October), normal irrigation and drought stress conditions (restricted irrigation after pod formation stage) was observed in Okapi and L109, respectively). Among genotypes, R15 line under delay planting (1 November) and both normal irrigation and drought stress conditions (restricted irrigation after pod formation stage) showed the maximum seed yield.